Effect of ACE Inhibitors, ARBs, and Other Antihypertensive Drugs on Hypertensive Patients with COVID-19 Infection - Shojaei, Seyedpouzhia; Nooraeen, Sara; Soroureddin, Zahra; Sedaghat, Meghdad; Ansar, Padideh; Rassouli, Sadaf; Goudarzi, Mehdi; Haghighi, Mehrdad (Novelty in Biomedicine, 2026)
Background: To investigate differences in disease severity and outcomes among COVID-19 patients with a history of hypertension using angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and other antihypertensive drugs. Materials and Methods: Based on drug exposure, 153 hypertensive patients with COVID-19 were divided into three groups: angiotensin-converting enzyme inhibitor group, angiotensin receptor blocker group, and other antihypertensive drugs group. The outcomes, laboratory and clinical results, were compared. Results: The frequency of ICU admission among patients in the angiotensin receptor blocker, angiotensin-converting enzyme inhibitor, and other antihypertensive drug groups was 25.5%, 27.8%, and 23.2%, respectively. The intubation frequency was 23.6%, 27.8%, and 30.4%, respectively. The longest hospital stay was observed in the angiotensin-converting enzyme inhibitor group, but the difference was not significant (P>0.05). The mortality rates were highest in the other antihypertensive drug groups. Conclusion: Patients with COVID-19 who consume angiotensin-converting enzyme inhibitors and angiotensin receptor blockers have lower mortality rates compared to patients consuming other antihypertensive drugs.